Support structures for legal mobilization : the case of the colombian trans movement (2017)
Under what conditions can social movements produce legal changes? Existing studies point to legal opportunities and support structures for legal mobilization as the key explanatory variables, but do not specify how exactly these variables interact. In addition, they have not adequately examined the process or relevance of building support structures. This article leverages variation in the strategies of two factions of the Colombian trans movement to show that, despite the presence of favorable legal opportunities, the determining factor for movements- legal success is the process through which they build support structures for legal mobilization, which in turn affects the kind of resources to which they have access. Particularly, support structures built through brokerage connect movements to a network of lawyers, which increases their chances for successful legal mobilization. This article draws on data gathered through 28 interviews to key actors, one year of participant observation, and documentary review.